Users' experience on airline chatbots - Arreza, Mariae Khrisna Baring; Esguerra, James Garcia (Penerbit Universiti Kebangsaan Malaysia, 2022)
A chatbot is an advancing technology that has taken the airline industry to a different level of service. The continuous pursuit drives this development to provide efficient and quality services; however, this technology is not void of challenges that may affect customers' experiences. This study utilizes a sequential mixed method approach that explored the Filipino experiences of using airline chatbots. The results revealed neutral users' experiences. The qualitative components revealed the following themes (1) Difficult experience; (2) Limitations of the chatbots; (3) Lack of human connections and; (4) Positive experiences. As a recommendation, further study may be required utilizing different indicators.